CONFLICT MANAGEMENT THROUGH BAILEO DESIGN CONCEPT STRATEGY IN YALAHATAN VILLAGE, CENTRAL MALUKU DISTRICT - Patty, Muhammad Darma; Wahjutami, Erlina Laksmiani (Border: Jurnal Arsitektur, 2024)
The Ambon conflict is an event of conflict between religious communities. What occurred in the period from 1999 to 2000, this event caused divisions which had an impact on the harmony of the people who had long lived side by side. Baileo House is a traditional building that is able to translate various elements of kinship between pela gandong and patasiwa, patalima. This research was conducted in Yalahatan hamlet, negeri Tamilouw, Central Maluku Regency. The people of Yalahatan hamlet have a Baileo house called usali or a community gathering place. The aim of this research is to identify various factors contained in the Baileo house in Yalahatan hamlet as a unifying building with its performance in minimizing conflict by elevating the community's identity as traditional people who love brotherhood. The type of research applied is qualitative descriptive research. From the research results, it was found that the performance of the Baileo house in uniting the Yalahatan hamlet community through its various functions, is an example of the existence of traditional values ​​which naturally direct the community to return to maintaining kinship relations between fellow Yalahatan people in particular and fellow Alifuru people in general.